2014
DOI: 10.2147/ijn.s68840
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen supersaturated fluid using fine micro/nanobubbles

Abstract: Microbubbles show peculiar properties, such as shrinking collapse, long lifetime, high gas solubility, negative electric charge, and free radical production. Fluids supersaturated with various gases can be easily generated using microbubbles. Oxygen microbubble fluid can be very useful for oxygen delivery to hypoxic tissues. However, there have been no reports of comparative investigations into adding fluids containing oxygen fine micro/nanobubbles (OFM-NBs) to common infusion solutions in daily medical care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 33 publications
4
63
1
Order By: Relevance
“…255,256,257,258 Moreover, the opportunity exists currently to further test the effects of supplemental O 2 ; more modern standards of clinical trials such as establishing dose/response, effects of treatment duration, minimum dosing necessary etc. should surely be attempted as a simple yet potentially effective intervention.…”
Section: Potential Drug Targets Of Important Placental Pathways Imentioning
confidence: 99%
“…255,256,257,258 Moreover, the opportunity exists currently to further test the effects of supplemental O 2 ; more modern standards of clinical trials such as establishing dose/response, effects of treatment duration, minimum dosing necessary etc. should surely be attempted as a simple yet potentially effective intervention.…”
Section: Potential Drug Targets Of Important Placental Pathways Imentioning
confidence: 99%
“…When MNBs are produced in water using oxygen or air as gas impregnated in their core, their negatively charged surface not only prevents them from merging together, which would cause them to lose their properties, but also attracts particulate matter and assists in the removal of debris . In addition, MNBs generate free radicals as they shrink, which potentially contributes to their antibacterial effects . Nanobubbles and microbubbles that shrink to become nanobubbles exist in a solution for different time periods depending on the conditions in which they are formed …”
Section: G Micro/nanobubblesmentioning
confidence: 99%
“…Matsuki et al was the first to apply MNBs to common infusions in daily medical care . They demonstrated that saline is the preferred solution for MNBs and that MNBs formed in dextran showed the highest pO 2 at 60 minutes .…”
Section: G Micro/nanobubblesmentioning
confidence: 99%
“…Bubble gas is important in the application of fine bubbles. For example, fluorocarbon microbubbles are preferably used as an ultrasound contrast reagent [22], whereas oxygen bubbles (OBs) are inevitably used for blood oxygenation [5,23].…”
Section: Introductionmentioning
confidence: 99%